History of ancient Greek scholarship : from the beginnings to the end of the Byzantine age - Montanari, Franco; Montanari, Franco (BRILL, 2020)
Intro -- Contents -- Introduction -- Chapter 1 The Origins and Growth of Scholarship in Pre-Hellenistic Greece -- 1 Social Premises and Conditions Leading to the Establishment of Scholarship -- 1.1 Reading and Writing in Archaic Greece -- 1.2 Writing, Literacy and the Development of New Media -- 1.3 Literacy as an Instrument in Learning -- 1.4 The Growth of Scholarly Environment -- 2 Social Institutions that Assisted in the Development of Scholarship -- 2.1 Education -- 2.2 Libraries and Archives -- 3 Philological Approaches in Pre-Alexandrian Greece -- 3.1 The Early Critical and Interpretative Approaches -- 3.2 The Beginnings of Homeric Textual Criticism and Editing -- 3.3 Early Text Exegesis and Literary Criticism -- 3.4 Fundamental Notions of Language Categories -- 3.5 Towards a Scholarly Methodology: the Development of Scholarly Self-Awareness -- 3.6 400 BC to Alexandria: an Overview -- Chapter 2 Hellenistic Scholarship -- 1 Preliminaries -- 1.1 Court Poetry and Scholarship in Hellenistic Societies -- 1.2 Historiographic Pattern -- 1.3 Scholarship and Knowledge -- 2 Alexandrian Scholarship to 144 BC -- 2.1 Traces of Scholarship Outside Alexandria in the Early Hellenistic Age -- 2.2 Culture and Royal Patronage in Early Ptolemaic Egypt: the Museum -- 2.3 Making the 'Universal' Library -- 2.4 Philology for Books, Books for Philology -- 2.5 Librarians' diadokhē and Learned Community -- 3 The Spread of Scholarship in the 2nd and 1st Centuries -- 3.1 Rise and Zenith of Pergamene Scholarship (2nd Century) -- 3.2 Pluralism and Exchange in Late Hellenistic Scholarship (144-31) -- 3.3 Alexandrian Scholars in an Augustan World -- Chapter 3 Greek Scholarship in the Imperial Era and Late Antiquity -- 1 State of Research, Presuppositions and Focal Points of a Historical Survey -- 2 Philology and Grammar in the Imperial Era and Late Antiquity in Context.